Can AI Detect Osteoporosis from X-rays? A Revolution in Opportunistic Screening - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Osteoporosis, often termed a "silent disease," is a major global health concern characterized by reduced bone mineral density BMD and a heightened risk of fr...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care